Body Dysmorphic Disorder Among Aesthetic Medicine Patients – A Literature Review - Surowaniec, Julia; Nowicki, Dawid; Muszyńska, Małgorzata; Karaś, Katarzyna; Mroszczyk, Sylwia (Quality in Sport, 2025)
Introduction: Body Dysmorphic Disorder (BDD) is a psychiatric disorder characterised by an excessive focus on perceived flaws in one’s appearance. It leads to a strong psychological distress, social withdrawal, and unnecessary aesthetic procedures. The rise of aesthetic medicine in the 21st century has made BDD an important clinical and ethical issue for practitioners. Aim of the study: This study aims to present the prevalence of BDD, its characteristics, diagnostic difficulties, and treatment. We also discuss ethical challenges associated with aesthetic medicine procedures and clinical management recommendations for aesthetic medicine practitioners. Materials and methods: A search of the literature review was performed using PubMed, Google Scholar, Scopus, and other databases. We focused primarily on studies published between 2017 and 2025. The following keywords and their combinations were used: “Body Dysmorphic Disorder”, “Aesthetic Medicine”, “Cosmetic Procedures”, “Psychiatry”, “Screening”, “Ethics”. Brief description of state of knowledge: BDD is more common in aesthetic medicine patients than in the general population and is influenced by social media and culture. Patients with BDD present alterations in the function and structure of the central nervous system. There are a few screening tools easy to use in the everyday practice of an aesthetician. Treatment includes pharmacotherapy and psychotherapy. Summary: BDD poses many clinical and ethical challenges. Cosmetic interventions alone rarely address underlying psychological distress long-term. Both cognitive-behavioural therapy and pharmacotherapy are useful tools in the treatment of BDD. Integrating screening and patient-centred approaches has the potential to improve safety, satisfaction, and long-term well-being in patients with this disorder.